Población y uso de hábitat del venado de páramo Odocoileus lasiotis (Artiodactyla: Cervidae) en Venezuela - Molina, Misael (1998)
Direct observations of Paramo's white-taí1ed deer were made along transecl in the Mucubají area (Parque N acional Sierra N evada, Mérida, Venezuela). Sex ratio was two does per buck. Group composition varied with time of year and reproductive condition. The reproductive cycle was similar to that of lhe white-tailed deer from the Costa Rican dry Pacific region. Acti vity was maximum between 9 - 11 h and 15 - 17 h, and minimum al night. T he deer feed on 13 species of vascular plants. (five families), and one of mushroom (Boletaceae: Agaricales). Fifteen plant species were used for shelter. Territory delimitation and signs for social communication were made primarily on gymnosperms (Cupressus and Pinus). Most deer were observed in terrain with slopes under 20% where the more complex and diverse vegetation associations exist.